A Double-ended Converter System with Two Different DC-buses Using Open Winding Permanent Magnet Machine for Traction Applications. Issue 15 (14th September 2017) - Li, Silong; Han, Di; Sarlioglu, Bulent
Abstract: In hybrid electric vehicles (HEVs), there are usually several different DC-buses of different voltage levels to handle different loads. DC–DC converters are used to transfer energy between different DC-buses. This paper proposed a double-ended converter for two different DC-buses with large voltage ratio. The high-voltage DC-bus is 600 V for the traction motor drive, while the low-voltage DC-bus is 48 V for the electronic devices on the vehicle. By using the proposed system configuration, energy could be transferred freely between the generator and the two loads, forming a very flexible powertrain. In addition, the weight, volume, and cost of power electronics components could be reduced. This paper introduced the operation principal and control algorithm of the proposed system. Simulations verified the functionality of the proposed system. The proposed system configuration is not only suitable for automotive applications, but can also be implemented in other applications, such as aerospace, marine, and industrial, where multiple DC-bus voltage levels are required.